Phase Response Identification of Photodetectors in High-Speed Interferometry Using Photoelectric Pseudorandom Signals - Yunke Sun; Yifei Xie; Xiaotong Yan; Xu Xing; Pengcheng Hu (IEEE Photonics Journal)
Dynamic accuracy and synchronization of high-speed interferometry are crucial for advanced manufacturing, semiconductor fabrication, and dynamic metrology, where asynchronous errors introduced by the nonlinear phase responses of photodetectors can severely degrade the measurement performance. The complex cross-physical processes make the phase responses of photodetectors challenging. Owing to their bandwidth, resolution, and test deviation limitations, the existing methods are not applicable to interferometric photodetectors. In this study, we employ a commonly available small form-factor pluggable module to generate optical pseudorandom signals as a photodetector’s excitation signals. Through correlation operations and phase spectrum analysis, the phase response of a photodetector with a 10-MHz bandwidth is identified with a model reliability of 90% and an uncertainty of 0.50° (k = 2). In practical applications, the identified phase response can help an interferometer suppress asynchronous errors to the sub-nm level within a maximum speed of 1.58 m/s. Comparative experiments verify the accuracy of the identified results and highlight substantial improvements in test precision, frequency resolution, practicality, and universality over existing methods.